EXPRESSION OF A PERSON'S PLACE IN SOCIETY IN GERMAN AND UZBEK LANGUAGES BY MEANS OF SOMATIC PHRASEOLOGY (Multidisciplinary Journal of Science and Technology, 2024)
In this article, somatic phraseologisms are studied by classifying them into phraseosemantic groups, and somatic phraseologisms denoting the place of people in society are analyzed into subgroups.